Mechanism of macroalgae Gracilaria bailiniae responding to cadmium and lanthanum - Huang, Bowen; Cui, Jianjun; Ran, Yu; Chen, Chunli; Li, Feng; Zhang, Yulei; Li, Zailiang; Xie, Enyi (Frontiers in Plant Science, 2022)
Abstract Macroalgae can accumulate a wide array of metals, leading to their appliance as biomonitors of aquatic environments. With the rapid development of industrial and agricultural-based activities, Cd pollution in aquatic environments is considered an increasingly severe problem worldwide. Although La could alleviate the Cd stress in higher terrestrial plants, the response mechanisms of macroalgae to Cd and La are unknown. Along these lines, in this work, Cd significantly affected the growth, internal cellular structure, photosynthesis, pigment content, antioxidant enzyme activity, and lipid peroxidation level of G. bailiniae. However, the presence of La alleviated these adverse effects from Cd. Furthermore, the response mechanism of G. bailiniae to Cd was attributed to the self-antioxidant ability enhancement, membrane defense, and programmed-cellular regulation. However, the presence of La mediated the biosynthesis of both flavonoids and lipids, which inhibited the Cd accumulation, modulated algal stress signalling networks, renewed the impaired chlorophyll molecule, maintained the activity of the crucial enzyme, enhanced antioxidant ability, and maintained the stabilization of redox homeostasis, alleviating the adverse impact from Cd and improve the growth of G. bailiniae. The experimental results successfully demonstrate a new detoxicant to alleviate Cd stress, promoting a more comprehensive array of macroalgal applications.